2009
DOI: 10.1158/1078-0432.ccr-09-0385
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Signatures in Barrett's Esophagus and Esophageal Adenocarcinoma

Abstract: Purpose: Esophageal adenocarcinoma is a highly aggressive malignancy that frequently develops from Barrett's esophagus, a premalignant pathologic change occurring in the lower end of the esophagus. Identifying Barrett's esophagus patients at high risk of malignant transformation is essential to the prevention of esophageal adenocarcinoma. Although microRNA (miRNA) expression signatures have been associated with the etiology and prognosis of several types of cancers, their roles in the development of esophageal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 55 publications
10
97
2
5
Order By: Relevance
“…In addition, we reported that miR-103/ 107 have a potential to serve as a prognostic marker (22), which is consistent with other recent studies in which miR-103/107/129 play a role in the development and progression of Barrett's associated adenocarcinoma and ESCC (20,24). In this study we showed that the relative expression of miR-92a is significantly correlated with lymph node metastasis and TNM stage of ESCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we reported that miR-103/ 107 have a potential to serve as a prognostic marker (22), which is consistent with other recent studies in which miR-103/107/129 play a role in the development and progression of Barrett's associated adenocarcinoma and ESCC (20,24). In this study we showed that the relative expression of miR-92a is significantly correlated with lymph node metastasis and TNM stage of ESCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Among miRNAs found to be downregulated during EAC development, let-7 family of miRNAs is tumor-suppressive and negatively regulates Ras oncogene. Fassan and colleagues confirmed upregulation of HMGA2, which is one of the target of let-7 miRNA, using immunohistochemistry in tissue samples (110,112,114). Further studies in the regards of miRNA and miRNA target genes will improve the biologic understanding of EAC pathogenesis and may also provide novel molecular targets for disease intervention.…”
Section: Cell Cycle-related Abnormalitiesmentioning
confidence: 94%
“…6 In various cancers, miRNAs have been demonstrated to regulate oncogenes or tumour suppressor genes. [7][8][9][10] In oesophageal carcinoma, different levels of miRNAs can be used to discriminate between benign and malignant oesophageal tissues, [11][12][13][14][15][16][17][18][19][20][21] and miRNAs are involved in cell proliferation, invasion, migration, apoptosis, cell cycle and tumorigenesis. [14][15][16]18,21,22 Most importantly, expression of miRNAs or RNASEN (enzyme in the biogenesis of miRNAs) correlates with the risk of lymph node metastasis, venous invasion, 21 and prognosis.…”
Section: Introductionmentioning
confidence: 99%